The Impact Of Green Accounting And Environmental Performance On Firm Value Of Mining Companies Listed On The Indonesia Stock Exchange - Alfiyani Khusnin Nashriyah; Musviyanti Musviyanti (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to examine the effect of green accounting and environmental performance on firm value in mining sector companies listed on the Indonesia Stock Exchange (IDX). Signaling theory is employed as the theoretical framework to explain how the implementation of green accounting and environmental performance may influence firm value. This study adopts a quantitative research approach using secondary data obtained from annual reports and sustainability reports of mining companies during the 2020–2024 period. The sample consists of 14 companies selected through purposive sampling. Data were analyzed using multiple linear regression analysis. The findings reveal that green accounting has a significant effect on firm value, indicating that greater environmental responsibility disclosure and environmental cost allocation are positively perceived by investors. In contrast, environmental performance does not have a significant effect on firm value. These results suggest that investors place greater emphasis on the disclosure of environmental accounting information than on environmental performance ratings when assessing firm value. This study contributes to the literature on sustainability accounting and provides insights for companies seeking to enhance their value through environmental practices.